Mitochondria-targeted platinum(ii) complexes: dual inhibitory activities on tumor cell proliferation and migration/invasion via intracellular trafficking of β-catenin. Issue 6 (17th May 2017) - Li, Jingling; He, Xiaoli; Zou, Yeling; Chen, Dandan; Yang, Liecheng; Rao, Jiaming; Chen, Huabing; Chan, Michael C. W.; Li, Lin; Guo, Zhengqing; Zhang, Leshuai W.; Chen, Chunying
Abstract : PIP-platin targets on mitochondria for inhibition of cell proliferation and migration through translocation of β-catenin. Abstract : Mitochondria-targeted therapy is an alternative strategy for cancer therapy and may overcome the problems of metastasis and drug resistance that usually occur in conventional treatment. In this work, we demonstrate the mitochondria-targeted delivery of a cationic cyclometalated platinum(ii ) complex, PIP-platin, in cancer cells. PIP-platin showed selective delivery and accumulation in the mitochondria and exhibited toxicity against a variety of tumor cell lines. The mitochondria were disrupted by PIP-platin, along with the generation of reactive oxygen species, depolarization of mitochondrial membrane potential, release of cytochrome c and necrosis. Interestingly, PIP-platin can promote cell adhesion within several hours and the cells became hard to dislodge from the culture plate. A wound healing assay, transwell migration/invasion assay and 3D spheroid migration assay all demonstrated that PIP-platin can inhibit cell migration/invasion. To illustrate the associated mechanisms, we investigated the intracellular trafficking of β-catenin, a central protein in the regulation of cell adhesion, and gene transcription for cell proliferation. Upon treatment with PIP-platin, this protein can translocate onto the plasma membrane for increased cell adhesion. In addition, PIP-platin was demonstrated to efficiently inhibit Wnt signaling by blocking the translocation of β-catenin into the nuclei, thereby preventing cell proliferation. We demonstrate that, accordingly, PIP-platin has remarkable potential for intracellular delivery in mitochondria and has inhibitory effects on cancer cell proliferation and migration/invasion through β-catenin, and may therefore be exploited as a dual-functional antitumor drug candidate in cancer treatment.